1984
DOI: 10.1007/bf01820878
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic dykes in the north Chilean Coast Range

Abstract: ZusammenfassungDie nordchilenisehe Kiistenkordillere wird von einem dichten Netz vorwiegend marlscher G~inge durehzogen. Es sind dies keine Lamprophyre, sondern sie stellen Zufuhrsysteme effusiver T/~tigkeit im Zeitraum Jura bis Unterkreide dar.Die Ganggesteine lassen sich petrographisch und aufgrund Haupt-und Spurenelementehemischer Charakteristika in drei Serien einteilen. Die ~ltere alkaline Serie I zeichnet sich durch erh6hte Na-, K-, Fe-, Ti-, Mn-, P-, V-sowie niedrige A1-und Sr-Gehalte aus. Die Basalte u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Additional studies have been done on their secondary alteration and associated copper mineralization by Losert (1973) and their petrography and geochemistry by Palacios (1978). Pichowiak and Breitkreuz (1984) suggested that dike rocks in the La Negra Formation have withinplate geochemical affinities and formed in an ensialic setting.…”
Section: Previous Workmentioning
confidence: 98%
See 1 more Smart Citation
“…Additional studies have been done on their secondary alteration and associated copper mineralization by Losert (1973) and their petrography and geochemistry by Palacios (1978). Pichowiak and Breitkreuz (1984) suggested that dike rocks in the La Negra Formation have withinplate geochemical affinities and formed in an ensialic setting.…”
Section: Previous Workmentioning
confidence: 98%
“…2). Only the youngest plutonic complexes are not penetrated by basic dikes (Pichowiak and Breitkreuz, 1984).…”
Section: Geologic Settingmentioning
confidence: 99%